Evaluating ASEAN and EU Banking Sector Efficiency Using DEA (Data Envelopment Analysis) - Putri, Jessica Amanda; Sudrajad, Oktofa Yudha; Kabir, Rezaul (The Asian Journal of Technology Management (AJTM), 2023)
Abstract. This study compares ASEAN and EU banking efficiency using Data Envelopment Analysis (DEA) and an intermediary approach. Three input variables (staff expense, fixed assets, total customer deposits) and two output variables (loans to customer and operating income other than interest) are analyzed using RStudio and R. EU and ASEAN banks had efficiency scores of 0.7 and 0.65, respectively, showing opportunity for improvement. Based on cost analyses, ASEAN banks are more efficient than their EU counterparts. Inefficiencies occur when output surpasses input or is much lower than another output variable. However, both regions may improve banking efficiency to do better. The 10-year trends exhibit oscillations, showing that regulatory issues affect banking efficiency. Stricter laws, higher capital requirements, and risk management changes may have hampered ASEAN credit. The dynamics and objectives of the EU and ASEAN economic blocs shape their financial systems. ASEAN is working toward regulatory convergence, while the EU has integrated and harmonized more. To maintain a stable and efficient financial industry, the region's banks must adapt to changing economic landscapes, technological advances, and mounting challenges.  Keywords:  ASEAN, bank performance, data envelopment analysis, efficiency, EU